A Theological Review of Approaching Models in the Dialog of Faith and Science - Ridwanta Manogu (Diligentia: Journal of Theology and Christian Education, 2019)
Scholars have been proposing numerous models in “reconciling” faith and science. All proposed models, generally, could be categorized into four approaches: conflict, independence, dialogue, and integration. Since models in approaching the dialog of faith and science, basically, express presuppositions of how someone view reality. In this essay, therefore, these models are reviewed in the light of how Christians should comprehend the reality through the Scripture: God reveals Himself in two ways, general and special. General revelation is the world as His creation, and special revelation is the His words that have been written in the Bible. Special revelation, fundamentally, is a metaphysical framework for Christians to understand God’s creation. As the result, approaching model which cohere to biblical concept of one truth is integration model, which is, as some scholars call, the reconstruction or paradigmatic approach.